2016
DOI: 10.1016/j.bbagrm.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of H1 linker histones in mammalian development and stem cell differentiation

Abstract: H1 linker histones are key chromatin architectural proteins facilitating the formation of higher order chromatin structures. The H1 family constitutes the most heterogeneous group of histone proteins, with eleven non-allelic H1 variants in mammals. H1 variants differ in their biochemical properties and exhibit significant sequence divergence from one another, yet most of them are highly conserved during evolution from mouse to human. H1 variants are differentially regulated during development and their cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 195 publications
(309 reference statements)
4
68
0
Order By: Relevance
“…H1 proteins are evolutionarily unrelated to the core histones and are characterized by a central winged helix domain, or globular domain, flanked by unstructured N-and C-termini (Cerf et al 1993;Ramakrishnan et al 1993;Kasinsky et al 2001). Early studies showed that animal H1 proteins bind outside of the NCP (Baldwin et al 1975;Shaw et al 1976) and can protect an additional 20bp of DNA from nuclease In vivo studies of mammalian H1 are complicated by the existence of 11 H1 variants that appear to be partially redundant (Pan and Fan 2015). Deletion of single H1 variants failed to produce significant phenotypes in mice (Fan et al 2001), but mice lacking three H1 variants are inviable (Fan et al 2003) and triple-knockout embryonic stem cells (ESCs) are unable to differentiate (Zhang et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…H1 proteins are evolutionarily unrelated to the core histones and are characterized by a central winged helix domain, or globular domain, flanked by unstructured N-and C-termini (Cerf et al 1993;Ramakrishnan et al 1993;Kasinsky et al 2001). Early studies showed that animal H1 proteins bind outside of the NCP (Baldwin et al 1975;Shaw et al 1976) and can protect an additional 20bp of DNA from nuclease In vivo studies of mammalian H1 are complicated by the existence of 11 H1 variants that appear to be partially redundant (Pan and Fan 2015). Deletion of single H1 variants failed to produce significant phenotypes in mice (Fan et al 2001), but mice lacking three H1 variants are inviable (Fan et al 2003) and triple-knockout embryonic stem cells (ESCs) are unable to differentiate (Zhang et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…This cluster included sets of histone H1 genes that are transcribed with cell cycle-dependent and independent control, which suggests that the difference in the chromatin organisation of this region between pluripotent states is likely to be driven by additional factors that act outside of the cell cycle. Given that the expression and regulation of individual H1 isoforms varies substantially between cell types and these properties are associated closely with pluripotency, differentiation and development (Pan and Fan, 2016;Turinetto and Giachino, 2015), a focused examination of histone H1 function in these cell types would be an interesting future direction of research. More commonly though, we discovered that sub-networks tended to be larger and to contain a greater number of interactions in primed compared to naïve PSCs.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Conversely, the cluster H1 members are induced through the major zygotic gene activation, and incorporated into the chromatin. 9 To date, each of the somatic H1 members (H1f0, and H1.1-H1.5) has been investigated only as a percentage of the total histones in midgestation embryos, 10,11 and the individual expression patterns in the subsequent stages of embryogenesis have not been fully defined. H1f0 is rarely expressed during embryogenesis; rather, it is accumulated in the terminally differentiated cells at the postnatal stage.…”
Section: Research-article2017mentioning
confidence: 99%
“…Although the single-knockout mice of each H1 variant are phenotypically normal, 17,18 the triple-knockout mice of H1.2, H1.3, and H1.4 caused the embryonic lethality at E11.5 by a broad spectrum of developmental defects. 11,19 In terms of H1fx protein, there has been no report about its expression pattern during mammalian embryogenesis. H1fx is the most recently identified and thus the least characterized of the H1 family members.…”
Section: Research-article2017mentioning
confidence: 99%